Revisiting Walter Benjamin’s “The Task of the Translator” in Light of His Concept of Criticism in German Romanticism - St. André, James (TTR, 2011)
Walter Benjamin’s essay “The Task of the Translator,” the most widely cited twentieth century philosophical statement on translation, is commonly seen as one of the most opaque and misunderstood essays in the field. This paper uses a close reading of Benjamin’s doctoral thesis, “The Concept of Criticism in German Romanticism,” to throw light on his thoughts on translation. I argue that the German Romantics’ definition of art, and art’s relation to criticism, are crucial to understanding why Benjamin conceived of translation as an “afterlife” of the work of art, why he believed that translatability is an innate quality of the work of art, and why he speaks of translation as moving the work of art onto a higher plane. I read Benjamin’s own essay on translation as a sort of “criticism” which seeks to “translate” the philosophical ideals of the Romantics, and thus give them an afterlife, and then reflect upon the implications for translation studies today.